The effect of on-site and outreach-based needle and syringe programs in people who inject drugs in Kermanshah, Iran - Nazari, S.; Noroozi, M.; Soori, H.; Noroozi, A.; Mehrabi, Y.; Hajebi, A.; Sharifi, H.; Higgs, Peter; Mirzazadeh, A. (Elsevier BV, 2016)
Background: Needle and syringe programs (NSPs) are widely used to reduce harms associated with drug injecting. This study assessed the effect of facility-based (on-site services at drop-in centre) and outreach models of NSP on injection risk behaviours. Methods: Self-reported data from 455 people who injected drugs (PWID) during 2014 in Kermanshah, Iran, were examined to measure demographic characteristics and risk behaviors. Self-reported and program data were also assessed to identify their main source of injection equipment. Participants were divided into three sub-groups: facility-based NSP users, outreach NSP users and non-users (comparison group). Coarsened exact matching was used to make the three groups statistically equivalent based on age, place of residence, education and income, and groups were compared regarding the proportion of borrowing or lending of syringes/cookers, reusing syringes and recent HIV testing. Results: Overall, 76% of participants reported any NSP service use during the two months prior to interview. Only 23% (95%CI: 17-27) reported outreach NSP as their main source of syringes. Using facility-based NSP significantly decreased recent syringe borrowing (OR: 0.27, 95%CI: 0.10-0.70), recent syringe reuse (OR: 0.38, 95%CI: 0.23-0.68) and increased recent HIV testing (OR: 2.60, 95%CI: 1.48-4.56). Similar effects were observed among outreach NSP users; in addition, the outreach NSP model significantly reduced the chance of lending syringes (OR: 0.31, 95%CI: 0.15-0.60), compared to facility-based NSP (OR: 1.25, 95%CI: 0.74-2.17). Conclusion: These findings suggest that the outreach NSP model is as effective as facility-based NSP in reducing injection risk behaviours and increasing the rate of HIV testing. Outreach NSP was even more effective than facility-based in reducing the lending of syringes to others. Scaling up outreach NSP is an effective intervention to further reduce transmission of HIV via needle sharing.